2005
DOI: 10.1021/jp054053k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigations of the Inelastic and Reactive Scattering Dynamics of O(3P) + D2

Abstract: This paper presents a combined experimental and theoretical study of the dynamics of O((3)P) + D(2) collisions, with emphasis on a center-of-mass (c.m.) collision energy of 25 kcal mol(-1). The experiments were conducted with a crossed-molecular-beams apparatus, employing a laser detonation source to produce hyperthermal atomic oxygen and mass spectrometric detection to measure the product angular and time-of-flight distributions. The novel beam source, which enabled these experiments to be conducted, contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(149 citation statements)
references
References 39 publications
(65 reference statements)
8
141
0
Order By: Relevance
“…1͑a͔͒ increases with increasing collision energy, and the reactive energy threshold of about 0.40 eV agrees well with a previous quantum single surface study on the O͑ 3 P͒ +H 2 reaction. 24 This is consistent with a barrier process. A similar increasing trend is found in the three cross sections caused by intersystem crossing ͓see Figs.…”
Section: Computational Aspectssupporting
confidence: 80%
“…1͑a͔͒ increases with increasing collision energy, and the reactive energy threshold of about 0.40 eV agrees well with a previous quantum single surface study on the O͑ 3 P͒ +H 2 reaction. 24 This is consistent with a barrier process. A similar increasing trend is found in the three cross sections caused by intersystem crossing ͓see Figs.…”
Section: Computational Aspectssupporting
confidence: 80%
“…To obtain satisfactory fits to the experimental data, two separate sets of P(E) and T(θ) distributions were used in the forward-convolution fitting procedure, with one for forward scattering and one for backward scattering. As discussed at length previously, 41 the derived c.m. angular and translational energy distributions are not entirely unique because of the limited resolution of the data.…”
Section: Resultsmentioning
confidence: 72%
“…quantities from the laboratory TOF and angular distributions. [41][42][43][44] A supersonic expansion of HCl was created with a piezoelectric pulsed valve, with a nozzle diameter of 1.0 mm, from a stagnation pressure of 15 psig. The HCl beam passed through a 5-mm-diameter skimmer and a 3-mm-diameter aperture before crossing the O-atom beam.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Classical results reproduce the coupling effect fairly well, especially at high energies where quasiclassical TSH calculations indicated enhanced reaction probabilities ͑compared to the single surface probabilities͒. 10 Introduction of the linearized quantum force corrects single surface quantum effects in the dynamics and improves agreement with the QM probabilities. Inclusion of the exponential function into the basis gives accurate reaction probabilities.…”
Section: Discussionmentioning
confidence: 82%
“…7 Maiti and Schatz have used TSH to study spin-orbit interaction induced intersystem crossing effects in the O + H 2 reaction, including four PESs in this model. 8 This reactive system has been thoroughly investigated both experimentally and theoretically, [9][10][11][12] although the first quantum wave-packet study involving four coupled electronic surfaces has been reported only recently. 13 Accurate PESs are available due to Rogers et al 14 and Dobbyn and Knowles, 15 and the spin-orbit couplings have been determined by Hoffmann and Schatz.…”
Section: Introductionmentioning
confidence: 99%